Correlation between vitamin D levels, individual and socio-demographic characteristics and COVID-19 infection and death rates in 20 European countries: A modelling study - John C. DEARDEN; Philip H. ROWE (Journal of Health and Social Sciences)
Introduction: Numerous potentially controlling demographic factors such as age, poverty, obesity, and car- diovascular and respiratory co-morbidities have been suggested, and high vitamin D levels have been found, to be associated with lower levels of COVID-19 infection. This study aimed to explore the correlation between vitamin D levels and socio-demographic characteristics with COVID-19 cases and deaths in 20 European countries. Methods: A quantitative ecological study was designed. Multiple linear regression analysis was used to examine which of vitamin D levels and 20 demographic factors correlated well with COVID-19 cases and deaths up to 9 May 2020 in 20 European countries. Data distributions were normalised by the Box and Cox approach and the Minitab routine ‘Best Subsets’ was used to select the best descriptor sets for each quantitative model of cases and deaths. Results: Cases were best modelled by vitamin D levels, stroke deaths, respiratory deaths, smoking, and human development levels. Deaths were best modelled by the number of cases, stroke deaths, proportion of African/Afro-Caribbean people, proportion of over 65-year-olds, population density, and levels of physical inactivity. Good correlations were obtained for each model, with coefficients of determination (r2) being around 0.7 or greater. The correlation of cases with vitamin D levels, stroke deaths, and respiratory deaths was r2 = 0.712, while the correlation of deaths with population density, levels of physical inactivity, and stroke deaths was r2 = 0.745. Discussion and Conclusions: These results help to explain the variability of COVID-19 cases and deaths, and offer guidance in planning against future coronavirus pandemics. Controlling for a wide range of factors reduces the risk that the apparent protective effect of vitamin D might be confounded.